Law Enforcement for Lawyers Committing Contempt of Court in The Criminal Justice System in Indonesia with Thailand - Haykal, Salman Daffa; Wulandari, Cahya (Postgraduate Program in Law, Pattimura University, 2025)
Introduction: Law enforcement against lawyers as perpetrators of contempt of court in the criminal justice system in Indonesia still faces significant challenges. The contempt of court case between lawyer Razman and Hotman Paris shows that the law enforcement process is still convoluted.Purposes of the Research: To examine the law enforcement against Advocates who commit contempt of court and to compare law enforcement with Thailand.Methods of the Research: This research uses a quantitative juridical-normative method through a statute approach by comparing the legal foundations in the enforcement of contempt of court.Results Main Findings of the Research: The findings indicate that in Indonesia, law enforcement is still convoluted as it goes through the reporting process via the police, then the prosecutor's office, and the court. This is different from Thailand, where Article 33 of the Civil Procedure Code states that a judge can impose a penalty on the suspect without going through the reporting process to the police and so on. Therefore, there is a need for an article that accommodates the law enforcement process for lawyers committing contempt of court during the trial.